Thermocline Storage Tank with Concrete Filler - Margarita Manuela Rodríguez-García; Esther Rojas; Alain Ferriere; Lester Padilla; Juan Manuel Caruncho (SolarPACES Conference Proceedings, 2024)
A thermal storage of 2500 kWh is designed, built and installed at the site of the experimental solar tower of Themis in Targasonne (France) within the POLYPHEM project (H2020 program, Ref N. 764048). The thermal energy storage (TES) consists of a thermocline tank with solid filler and thermal oil as heat transfer fluid. Tank walls, filler bricks and foundations are made of concrete. This new concept introduces some challenges that have been addresed during the construction and commissioning of the TES system. In this paper, authors present the main issues and solutions adopted for the tank design and construction.